Immunocheckpoint Inhibitor- (Nivolumab-) Associated Hypereosinophilia in Non-Small-Cell Lung Carcinoma - Navdeep Singh; Sandeep Singh Lubana; George Constantinou; Andrea N. Leaf (Case Reports in Oncological Medicine)
Immunocheckpoint inhibitor (ICI) therapy has provided significant clinical improvements in the treatment of several malignancies. The purpose of this report is to increase awareness of hypereosinophilia associated with checkpoint inhibitors, a topic that has been rarely reported. Hypereosinophilia may need to be addressed especially if eosinophil counts increase to levels where hypereosinophilic visceral complications can occur. We are presenting a case of a 57-year-old male with hypereosinophilia that was seen in the setting of progression of metastatic non-small-cell lung cancer during and after nivolumab treatment.